(3GOGQI GdeHjYGJs - (3Ydj YHO GdQVG(B, (3GdLjGTjs ((3YeGf(B:s (3OGQ hGFd ddfTQ h GdJhRjY(B,s, 2003)
(3Ef GOGQI GdeHjYGJ gj GdGOGQI GdJj JJhdi YedjI GdeHGOdI hGdJj JYJHQ HhGHI GdefTCI Ydi GdShb(B. (3jbY GdcJGH aj NeSI CLRGA JJaQY efg GdaUhd Ydi GdfMhGdJGdj(B: (3GdaUhd GdChdi JfGhdJ GdeONd dGOGQIGdeHjYGJ heGgjI EOGQI GdeHjYGJ hGdHjY GdTNUj hJfXje GdeHjYGJ hJfXje JMajR Gdbhi GdHjYjI, hJfGhdJ GdaUhd GdGNQi GdMhGaR hecGaCI QLGd GdHjY hJNWjW GdeHjYGJ heGgjI GdJfHD HGdeHjYGJ hCSGdjH GdJfHD HGdeHjYGJ hGdejRGfjI GdJbOjQjI ddeHjYGJ hJNWjW hGbGeI efGWb GdHjY hJNWjW hJchjf GdMUU GdHjYjI, GdGLRGA GdCNjQI JMOKJ Yf QbGHI hJbjje COGA GdCfTWI GdHjYjI hJbjje hCOGA QLGd GdHjY hGOGQI GdeHjYGJ hCfXeI GdeYdheGJ hCfXeI GdeYdheGJ GdJShjbjI hCNjQG CfXeI OYe GdbQGQGJ GdJShjbjI(B.s
(3HjHdjhZQGajG (B: (3U(B. 353-358s
Keywords: (3GOGQI GdeHjYGJs; (3GdGShGbs